How Has the COVID-19 Pandemic Affected the Way We Access and Interact with the Countryside and the Animals within It? - Jo Hockenhull; Keith Squibb; Amelia Cameron (Animals, 2021)
There is growing evidence that the changes in human behaviour resulting from the COVID-19 pandemic have had positive and negative impacts on the natural world. This study used an online survey to explore how the first UK lockdown affected human exercising behaviour, with particular focus on the role of wild and domestic animals. The survey was completed by 308 respondents. There was a significant increase in the frequency that respondents went for walks outdoors during lockdown, in comparison to pre-lockdown levels (p ≤ 0.001), and this was sustained (albeit to a lesser extent) once lockdown ended (p = 0.005). Engaging with the natural world was an important feature of walks outside for 81% of respondents. A small proportion of respondents reported physically interacting with the animals they encountered and/or feeding them, which may have implications for their welfare. The findings suggest that those who value animal encounters during their time outside always seek these interactions, while those who do not, did not tend to change this behaviour following lockdown. Should the changes in human exercising behaviour be sustained, it is important to balance the benefits of walking outdoors for human health and wellbeing with the health and welfare of the animals they encounter.